Cylindrical shell hybrid finite elements - Edwards, Gordon (1974)
The work is concerned with the application of the hybrid finite element method to thin plate and cylindrical shell structures. One plate bending element and three shell elements are studied. The plate element is the same as one already appearing in the literature but it is also used here to form the basis of a flat triangular element for the analysis of shells.